INVESTIGATION OF CORRUPTION ON PROCUREMENT OF GOODS AND SERVICES (Study: Makassar District Attorney) - Ahsan Annur; Abdul Agis; Hamza Baharuddin (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal